Leveraging telemedicine for management of veterans with heart failure during COVID-19. Issue 1 (18th January 2022) - de Peralta, Shelly S.; Ziaeian, Boback; Chang, Donald S.; Goldberg, Sarah; Vetrivel, Reeta; Fang, Yichun M.
ABSTRACT: Background: Telemedicine and telemonitoring have become invaluable tools in managing chronic diseases, such as heart failure (HF). With the recent pandemic, telemedicine has become the preferred method of providing consultative care. Local Problem: This rapid paradigm shift from face-to-face (F2F) consultations to telemedicine required a collaborative approach for successful implementation while maintaining quality of care. The processes for conducting a telemedicine visit for HF patient are not well defined or outlined. Method: Using a collaborative practice model and nurse practitioner led program, technology was leveraged to manage the high-risk HF population using virtual care (consultation via phone or video-to-home) with two aims: first to provide ongoing HF care using available telemedicine technologies or F2F care when necessary and, second, to evaluate and direct those needing urgent/emergent level of care to emergency department (ED). Intervention: The process was converted into an intuitive algorithm that describes essential elements and team roles necessary for execution of a successful HF consultation. Results: Following the algorithm, nurse practitioners conducted 132 visits, yielding 100% success in the conversion of F2F appointments to telemedicine, with 3 patients referred to ED for care. The information obtained through telemedicine consultation accurately informed decision for ED evaluation with resultant admission. Conclusion: Collaborative team-based approach delineated in the algorithm facilitated successful virtual consultations for HF patients and accurately informed decisions for higher level of care.